2018
DOI: 10.1039/c7cc09484a
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of [Cu2(COO)4] and [M33-O)(COO)6] (M = Sc, Fe, Ga, and In) building blocks into porous frameworks towards ultra-high C2H2/CO2and C2H2/CH4separation performance

Abstract: A porous MOF platform (SNNU-65s) formed by creatively combining paddle-wheel-like [Cu(COO)] and trigonal prismatic [M(μ-O)(COO)] building blocks was designed herein. The mixed and high-density open metal sites and the OH-functionalized pore surface promote SNNU-65s to exhibit ultra-high CH uptake and separation performance. Impressively, SNNU-65-Cu-Ga stands out for the highest CH/CO (18.7) and CH/CH (120.6) selectivity among all the reported MOFs at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Therefore, the design of ZCOFs based on mixed types of metal clusters remains ag reat challenge. [131,132] Recently,Z hang et al reported aZ COF containing two kinds of tetrahedral metal clusters, at etrahedral [Cu 4 I 4 (ina) 4 ] 4À (ina = isonicotinic acid) cluster and ad istorted tetrahedral paddlewheel Mn 2 (COO) 4 (H 2 O)(dmf) cluster ( Figure 8). The [Cu 4 I 4 (ina) 4 ] 4À and Mn 2 (COO) 4 (H 2 O)(dmf) clustersb oth act as tetrahedral 4-connected nodes interconnected by ina ligandst of ormatwofold interpenetrated dia-type framework with large channels that are approximately 6.0 4.5 2 in size.…”
Section: Zcofs Based On Mixed Types Of Tetrahedral Metal Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the design of ZCOFs based on mixed types of metal clusters remains ag reat challenge. [131,132] Recently,Z hang et al reported aZ COF containing two kinds of tetrahedral metal clusters, at etrahedral [Cu 4 I 4 (ina) 4 ] 4À (ina = isonicotinic acid) cluster and ad istorted tetrahedral paddlewheel Mn 2 (COO) 4 (H 2 O)(dmf) cluster ( Figure 8). The [Cu 4 I 4 (ina) 4 ] 4À and Mn 2 (COO) 4 (H 2 O)(dmf) clustersb oth act as tetrahedral 4-connected nodes interconnected by ina ligandst of ormatwofold interpenetrated dia-type framework with large channels that are approximately 6.0 4.5 2 in size.…”
Section: Zcofs Based On Mixed Types Of Tetrahedral Metal Clustersmentioning
confidence: 99%
“…However, it is hard to control the reaction conditions to integrate two different tetrahedral metal clusters into one structure, because different metal clusters enjoy their own distinct chemical environments (e.g., acidic, basic, neutral, hydrophilic, oleophilic, etc.). Therefore, the design of ZCOFs based on mixed types of metal clusters remains a great challenge . Recently, Zhang et al.…”
Section: Design and Synthesis Of Zcofsmentioning
confidence: 99%
“…[10] Even combined with accessible functional sites such as OMSs, LBSs,orHBAs, smaller pore sizes (< 5.0 )primarily help to enhance C 2 H 2 /CO 2 selectivity, [7,11] but larger pore sizes (> 7.5 )t end to enable high C 2 H 2 uptake capacity (Figure 1). [5,12] So the development of strategies to precisely regulate the pore sizes of MOFs within the range of about 5.0-7.5 may be an effective route to break through the trade-off barrier between C 2 H 2 storage and C 2 H 2 /CO 2 separation.…”
Section: Introductionmentioning
confidence: 99%
“…19 CPs as a type of promising functional materials have received considerable attention because of their intriguing structural features as well as applications in luminescence sensing, magnetic property, gas storage, drug delivery, and so on. [20][21][22][23][24][25][26][27][28] Particularly, CPs as uorescent sensors have drew more concern owing to their superiority in long-term stability, efficiency, and operability. Simultaneously, much effort has been made to synthesize uorescent CP materials for detecting different types of target analytes, such as metal ions, 29,30 anions, 31,32 and small molecules.…”
Section: Introductionmentioning
confidence: 99%